RESISTENSI Salmonella spp. TERHADAP BEBERAPA ANTIBIOTIK PADA DAGING ITIK DI KABUPATEN BOGOR YANG DAPAT MEMENGARUHI KESEHATAN KONSUMEN (Resistance of Salmonella spp. to Several Antibiotics from Duck Meat in Bogor District that Could Influence Consumer Health) - Loisa, Loisa; Lukman, Denny Widaya; Latif, Hadri (Jurnal Kedokteran Hewan, 2016)
This study aimed to determine the presence of Salmonella spp. in duck meat and to identify the resistance of Salmonella spp. against several antibiotics in duck meat associated with food safety. Total of 52 meat samples of ducks was collected from 5 subdistricts in Bogor District, i.e., Cariu-Jonggol, Gunung Sindur, Klapanunggal, Parung Panjang, and Ciomas based on the assumption of 95% confidence level, 50% predicted prevalence, and 10% standard error. The results showed that three samples (5.8%) were positive Salmonella spp. The majority of Salmonella spp. isolated from duck meat showed resistance against erythromycin (66.7%), streptomycin (33.3%), and chloramphenicol (33.3%). Nevertheless, Salmonella spp. was still sensitive againts enrofloxacin, trimethoprim sulfamethoxazole, cephalothin, ampicillin, nalidixid acid, tetracycline, and gentamicin.